The Engineering Development Array: A Low Frequency Radio Telescope Utilising SKA Precursor Technology. (17th August 2017) - Wayth, Randall; Sokolowski, Marcin; Booler, Tom; Crosse, Brian; Emrich, David; Grootjans, Robert; Hall, Peter J.; Horsley, Luke; Juswardy, Budi; Kenney, David; Steele, Kim; Sutinjo, Adrian; et al.
Abstract: We describe the design and performance of the Engineering Development Array, which is a low-frequency radio telescope comprising 256 dual-polarisation dipole antennas working as a phased array. The Engineering Development Array was conceived of, developed, and deployed in just 18 months via re-use of Square Kilometre Array precursor technology and expertise, specifically from the Murchison Widefield Array radio telescope. Using drift scans and a model for the sky brightness temperature at low frequencies, we have derived the Engineering Development Array's receiver temperature as a function of frequency. The Engineering Development Array is shown to be sky-noise limited over most of the frequency range measured between 60 and 240 MHz. By using the Engineering Development Array in interferometric mode with the Murchison Widefield Array, we used calibrated visibilities to measure the absolute sensitivity of the array. The measured array sensitivity matches very well with a model based on the array layout and measured receiver temperature. The results demonstrate the practicality and feasibility of using Murchison Widefield Array-style precursor technology for Square Kilometre Array-scale stations. The modular architecture of the Engineering Development Array allows upgrades to the array to be rolled out in a staged approach. Future improvements to the Engineering Development Array include replacing the second stage beamformer with a fully digital system, and to transition to using RF-over-fibre for the signal output from first stage beamformers.